18.3k views
3 votes
Define f: R → Rand g: R → R by the formulas: f(x) = x +3 and g(x) = -x. Find the functions: a) gof b) fºg

1 Answer

2 votes

Answer: 1) gof(x) = -(x+3)

2) fog(x) = -x+3

Explanation:

Since we have given that

Define f: R → Rand g: R → R

And f(x) = x+3

g(x) = -x

We need to find the functions as follows:

1) gof is given by


gof(x)=g(f(x))=g(x+3)=-(x+3)

2) fog is given by


fog(x)=f(g(x))=f(-x)=-x+3

Hence, 1) gof(x) = -(x+3)

2) fog(x) = -x+3

User MWiesner
by
6.4k points